Gobernanza en el medio ambiente y el caso de políticas verdes para el gobierno local de San Pedro Garza García, México - García Fuentes, Gustavo Adolfo (2024)
Environmental governance is a crucial field in natural resource management and environmental protection. In this context, research was conducted focusing on environmental governance with a specific emphasis on San Pedro Garza García, to address how environmental policies are developed and the impact of governance on their evolution and implementation. This municipality in Nuevo León, Mexico, is known primarily for its economy but has recently focused on environmental initiatives. The research methodology involved text analysis to understand and evaluate public policies, legal documents, reports, and other written resources. The main findings were that it has made significant legislative advances, but there remains a substantial gap regarding the development and dissemination of information, as well as the monitoring of environmental programs.